Exposure to solvents and outcome of pregnancy in university laboratory employees. Issue 3 (August 1984) - Axelsson, G; Lütz, C; Rylander, R
Abstract : The outcome of pregnancy was studied among personnel employed in laboratory work at the University of Gothenburg between 1968 and 1979. A questionnaire was distributed to 782 women; the response rate was 95%. When the 1160 pregnancies were divided into those with and without exposure to organic solvents during laboratory work, a slightly increased, but not significant, difference in the miscarriage rate was found (relative risk (RR) 1.31, 95% confidence interval 0.89-1.91). No differences in perinatal death rates or the prevalence of malformations were found between infants whose mothers were exposed to solvents and those who were not. Shift work during pregnancy was related to a higher miscarriage rate (RR 3.2, 95% confidence interval 1.36-7.47). No relation between cigarette smoking and miscarriage rate was found, although birth weights were lower when the mother smoked during pregnancy.